Starch/ Polyvinyl Alcohol (PVA) Blend Bioplastics: Synthesis and Physicochemical Properties - Shrestha, Binod; Chapain, Khagendra; Shah, Sambridhi; Pandit, Rajesh (Journal of Nepal Chemical Society, 2023)
Starch-based bioplastics are prepared from the waste of food materials and are widely used as the short-lived biodegradable plastic for household and food packaging applications. In this work, glycerol plasticized starch (extracted from potato peels)bioplastics blended with Polyvinyl Alcohol (PVA) in various compositions (wt.-%) were prepared, and characterized using Fourier Transform Infrared (FTIR) spectroscopy and their physicochemical properties such as water absorption, biodegradable properties, and acid-base resistance were investigated. The FTIR spectra of starch-based bioplastics blended with PVA of the peak at 2924 cm-1 portrayed good compatibility between starch bioplastics and PVA. The water absorption test showed that the increase in starch proportion in starch/PVA blend increases water absorption capacity. The higher weight ratio of starch in starch/ PVA blend bioplastics degraded more rapidly than other bioplastics. Furthermore, the bioplastics of higher starch content resist acid and base for 45 and 42 hours respectively without being dissolved.